Dilema Etika Guru dalam Pengambilan Keputusan Pendidikan - Juhriyatul Jannah; Arrum Miranti; Sidrotul Fajriyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to explore the ethical dilemmas faced by teachers in educational decision-making and the factors that influence them. As moral role models, teachers are often confronted with complex situations where fundamental values conflict, such as justice versus mercy or individual versus community interests. The method used in this research is a literature review with a descriptive-qualitative analysis of various written sources, including books, journals, and official documents related to teacher professional ethics. The results indicate that ethical decision-making is influenced by internal factors (physical condition, emotional state, personality, and experience) as well as external factors (position, situation, and the influence of the school environment). This study also highlights the significant impact of stress on the quality of a teacher's decisions, which can hinder cognitive abilities, creativity, and job satisfaction. As a solution, the article outlines nine steps for ethical decision-making, ranging from identifying conflicting values to final reflection. The conclusion emphasizes that developing teacher competence in handling ethical dilemmas and providing institutional support for stress management are crucial for creating an educational environment with integrity